Exploring the Effects of Employer Brand Dimensions on Talent Retention: An Empirical Study in Chinese Private-owned Enterprises - LIN, ZHUOYA (2020)
Due to the fierce ‘war for talent’, organisations are entangled in the situation of talent shortage. The urgency of attracting, recruiting and retaining talented people become the core of every organisation. However, most of the prior studies focused on the role of employer brand on recruitment issues and prospective employees. Therefore, the purpose of this study is to explore the effect of various employer brand dimensions on current employees’ intention to stay in the company. Accordingly, there are seven dimensions identified through the previous studies, namely organisational culture, person-organisation fit, corporate reputation, CSR, compensation and benefits, training and development and work-life balance, and further proceed with the analysis. This study employed a quantitative approach for measuring the relationship between seven employer brand dimensions and talent retention. Data was collected from 234 respondents who work in private-owned enterprises in China’s IT industry via the web-based survey. Findings of the study demonstrated that among the seven dimensions, only person-organisation fit, compensation and benefits, and work-life balance could significantly influence talent retention. Organisations thereby are suggested to pay more attention to these three dimensions during the process of building a compelling employer brand to the existing employees, achieving the goal of retaining them. Furthermore, the limitations of the study and suggestions for future study are discussed. Keywords: Employer brand dimensions, Talent retention, Person-organisation fit, Compensation and benefits, Work-life balance, IT Industry